Common strategy to improve community detection performance based on the nodes' property. Issue 2 (25th April 2019) - Du, Wei; He, Xiaochen
Abstract : Improving the community detection algorithm is of great importance. The authors propose a novel method based on the nodes' property in order to detect the community structure. Given a detected community structure, in which nodes have their community signals, the value of the modularity can be changed if a node's community sign change to other communities' signs. Accordingly, the new method readjusts the affiliation between a node and its community in order to raise the modularity value. Experimental results of the detection for a list of open‐source networks show that the proposed algorithm can detect better community structure than classic methodologies based on modularity.